133 Aquaporin 4 antibody seropositivity and visual function in a UK cohort. Issue 3 (9th February 2012) - George, J; Kitley, J; Leite, M I; Jacob, A; Boggild, M; Elston, J; Palace, J
Abstract : Objectives: To identify clinical features of aquaporin 4 (AQP4) antibody positive optic neuritis (ON) in neuromyelitis optica (NMO) and NMO spectrum disorder (NMOSD) in a UK cohort. Methods: We performed a retrospective review of case notes of NMO and NMOSD patients referred to the joint UK National NMO service (based at Liverpool and Oxford) positive for AQP4 antibody by cell based assay between 2006 and 2011. The clinical features, visual acuity, visual perimetry, optical coherence tomography results and visual evoked responses were analysed. Results: 50 AQP4 antibody positive patients were identified. The optic neuronopathy was associated with severe sight impairment. However some NMO patients had a mild ON indistinguishable clinically from MS. Patients with isolated longitudinally extensive myelitis (LETM) and AQP4 antibodies did not show subclinical optic nerve abnormalities. Conclusions: AQP4 antibody optic neuritis is clinically expressed and generally causes severe optic nerve damage. In those without clinical features the antibodies do not cause asymptomatic evidence of damage unlike in Multiple sclerosis which is commonly associated with subclinical involvement. The factors that influence whether AQP4 antibodies cause ON require elucidating. DoH National Specialised Commissioning Team joint UK Neuromyelitis Optica Service.